Physical, Chemical, Organoleptic Characteristics, and Antioxidant Activity of Instant Cascara Powder with Additions of Ginger and Sappan Wood - Masahid, Ardiyan Dwi; Yulianingtyas, Resya Elen; Witono, Yuli; Nafi, Ahmad (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2024)
The aroma and taste of cascara products are generally mild, and the use of cascara powder also produces a blackish-brown extract color. To enhance both the taste and aroma, it is recommended to add ginger (Zingiber officinale) and sappan wood (Caesalpinia sappan). Ginger contains essential oils to enhance aroma and has antioxidant activity. On the the hand, the Brazilin compound in sappan wood provides a natural red color, and the polyphenols have antioxidant activity. This study aimed to determine the effects of adding ginger and sappan wood extracts on physical, chemical, and organoleptic properties, as well as the antioxidant activity of instant cascara powder, with a focus on selecting the best and most preferred formulation. A Completely Randomized Design (CRD) was used with one factor, namely concentration of ginger and sappan wood extracts. The treatment consisted of six levels, including F1 as control (cascara 100 g), F2 (cascara 70 g, ginger 5 g, and sappan wood 25 g), F3 (cascara 70 g, ginger 10 g, and sappan wood 20 g), F4 (cascara 70 g, ginger 15 g, and sappan wood 15 g), F5 (cascara 70 g, ginger 20 g, and sappan wood 10 g), and F6 (cascara 70 g, ginger 25 g, and sappan wood 5 g). The results showed that additions of ginger and sappan wood extracts impacted physical property, namely redness value, chemical properties including moisture, polyphenol content, and antioxidant activity, as well as all organoleptic parameters. The best and most preferred formulation was sample F2 which had a redness value of 6,39, moisture content of 2,62%, polyphenol content of 35,41 mg GAE/g, and antioxidant activity amounting to 64,5%. Moreover, the average value of color preference was 5,32 (somewhat like), fragrance 4,32 (neutral), taste 4,8 (neutral – somewhat like), and overall 4,84 (neutral – somewhat like).